REVERSE ENGINEERING OF COMPLEX SHAPED PARTS (Academic journal Industrial Machine Building Civil Engineering, 2017)
Modern automated design of complex shaped parts using CAD/CAM/CAE software facesthe task of creating a virtual 3D-model of an existing physical object, without reference to thesource documentary producer. This work is dedicated to the practical application of reversibledesigning of technology elements used in extreme downhill biking. Significant load leads todestruction of some parts of the equipment, but replacement of a unit is economicallydisadvantageous. Simulation of the idler lower pulley wheel of rear derailleur and creation ofattachment to the protective helmet are described in the paper.The aim of the present research is practical application of the knowledge, obtained in theclassroom with computer 3D-design of complex shaped parts, using a modern technology ofreverse engineering (modeling) by means of PowerSHAPE 2015 (Delcam Ltd, UK) andAutodesk Fusion 360 (USA) software.The work will be presented to the international student competition Delcam 2016 andwas awarded the second prize of the International 3D Modeling Competition 2016 at PavelSukhoi State Technical University of Gomel, Belarus.